The ruling on the marriage of a pregnant woman from an illegitimate relationship: A perspective from the ulama consultative assembly of North Aceh Regency, Indonesia - Muhammad Dastur; Ja'far Ja'far; Bastiar Bastiar; Umar Muhammad Noor (Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2024)
This article examines the thoughts of the Majelis Permusyawaratan Ulama (MPU) administrators of North Aceh Regency regarding the marriage of pregnant women out of wedlock. Although this is a field study, the research first explores the Islamic jurisprudence (fiqh) perspective on the discussed topic and then reviews the MPU administrators’ legal opinions on the matter. The study finds that, in Islamic jurisprudence, the permissibility of marriage for a pregnant woman out of wedlock is highly disputed based on the cause of the pregnancy. According to the Mâlikites and the Hanbalites, and agreed by Abû Yûsuf from the Hanafî school, the marriage is invalid due to adultery, whereas the Shâfi‘ites and Abû Hanifah considered it valid. Nevertheless, the marriage is deemed invalid if the woman is still pregnant during the ‘iddah period. The MPU of North Aceh states that the marriage of a pregnant woman out of wedlock is legally valid but prohibited (haram) due to the potential for lineage confusion. They advise against such marriages to prevent possible issues regarding lineage and other related rights.